Fiber concrete, well lid and preparation method of fiber concrete and well lid

By using silane-modified steel fibers and other modifiers in fiber concrete, the problems of insufficient flexural strength and rust of the manhole cover of steel fiber concrete are solved, and higher bearing capacity and durability are achieved.

CN119430802APending Publication Date: 2025-02-14GUANGDONG GUANGZE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411674201.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing steel fiber concrete used in manhole covers has problems of insufficient flexural strength and steel fiber rust, which affects its bearing capacity and service life.

Method used

By adopting specific combination distribution, the prepared fiber concrete uses silane-modified steel fibers, fly ash, polyvinyl formaldehyde glue and defoaming agent to improve the flexural strength, corrosion resistance and durability of the concrete.

Benefits of technology

It significantly improves the flexural strength and durability of the steel fiber concrete manhole cover, and enhances its bearing capacity and corrosion resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses fiber concrete, a well lid and a preparation method of the well lid, and relates to the field of well lids. The fiber concrete comprises the following raw materials in parts by weight: 180-230 parts of cement; 310 to 350 parts of broken stone; 220 to 270 parts of quartz sand; 18 to 23 parts of silane modified steel fiber; 38 to 43 parts of fly ash; 1-2 parts of a water reducing agent; 2.4 to 3.8 parts of polyvinyl formal glue; 42 to 49 parts of water; and 0.1-0.3 part of a defoaming agent. The breaking strength and corrosion resistance of the prepared fiber concrete are improved, and the prepared well lid is high in bearing capacity and good in durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of manhole covers, and in particular to a fiber concrete and a manhole cover and a preparation method thereof. Background Art

[0002] Fiber concrete is a new type of building material that evenly distributes short and fine dispersed fibers in the concrete matrix to improve the performance of concrete. Compared with ordinary concrete, fiber concrete has high crack resistance, that is, high tensile, bending and fatigue resistance, and good toughness, that is, high impact resistance. As a type of fiber concrete, steel fiber concrete has excellent crack resistance and impact resistance, and has excellent performance in wear resistance, fatigue resistance and crack control. Steel fiber concrete is widely used in municipal roads, bridges, slope protection, construction and other engineering fields.

[0003] Manhole covers are closed at the top of the entrances and exits leading to underground facilities. They are required to be installed in places where public facilities such as tap water, telecommunications, electricity, gas, heat, fire protection, and sanitation are installed. Steel fiber concrete manhole covers are a type of composite manhole cover. The recycling value of steel fiber concrete is small. By replacing cast iron materials with steel fiber concrete to make manhole covers, the problem of cast iron manhole covers being frequently stolen can be solved. At the same time, steel fiber concrete manhole covers are inexpensive and have stable fatigue resistance, making them suitable for promotion.

[0004] The steel fiber concrete currently used for manhole covers still has the problem of insufficient flexural strength. At the same time, the steel fibers of the steel fiber concrete are prone to rust during long-term use, which affects the bearing capacity and service life of the steel fiber concrete manhole covers. Summary of the invention

[0005] In order to improve the flexural strength and corrosion resistance of steel fiber concrete used for manhole covers, the present application provides a fiber concrete and a manhole cover and a preparation method thereof.

[0006] The fiber concrete and manhole cover and the preparation method thereof provided in the present application adopt the following technical solutions: In a first aspect, the present application provides a fiber concrete comprising the following raw materials in parts by weight: 180-230 parts of cement; 310-350 parts of crushed stone; Quartz sand 220-270 parts; 18-23 parts of silane modified steel fiber; 38-43 parts of fly ash; 1-2 parts of water reducing agent; 2.4-3.8 parts of polyvinyl formal glue; 42-49 parts of water; Defoaming agent 0.1-0.3 parts.

[0007] By adopting the above technical scheme, the present application prepares concrete by combining specific components, and the prepared concrete has excellent flexural strength, corrosion resistance and durability, and the manufactured steel fiber concrete manhole cover has large bearing capacity and strong durability.

[0008] In fiber concrete, silane-modified steel fiber is selected. The bonding strength between steel fiber and cement matrix is ​​improved through silane modification, and the interface transition zone between steel fiber and cement matrix is ​​improved, so that the bridging and reinforcing effect of steel fiber can be more fully exerted to control the generation of cracks; at the same time, silane forms a surface coating on the surface of steel fiber, which is beneficial to the improvement of steel fiber anti-corrosion and the durability of steel fiber concrete manhole cover. The addition of fly ash can reduce the enrichment of calcium hydroxide content and increase the interfacial bonding force. The addition of polyvinyl alcohol formal glue can react with cement components to increase bonding force, fill the gaps in cement to enhance toughness, and improve the interface structure between steel fiber and cement matrix together with silane, so that the flexural strength and toughness of concrete are improved, and the bearing capacity and durability of concrete manhole cover are improved. Defoaming agent is used to eliminate the foam effect introduced by the addition of polyvinyl alcohol formal glue to concrete.

[0009] Optionally, the silane-modified steel fiber is prepared by the following steps: Mix water, methanol and silane in a volume ratio of (5-6):(1-1.3):1, add acetic acid to adjust the pH to 4-6 to obtain a silane hydrolyzate, add a hexafluorozirconic acid aqueous solution to the silane hydrolyzate to obtain a silane hydrolyzate having a mass fraction of hexafluorozirconic acid of 6%-9%; The steel fiber was polished with sandpaper, soaked in sodium hydroxide solution for 30-40 min, taken out, washed with deionized water and ethanol, and dried naturally; The air-dried steel fiber is immersed in a silane hydrolyzate, taken out and placed in an oven at 100-110° C. for drying to obtain a silane-modified steel fiber.

[0010] By adopting the above technical scheme, the steel fiber is polished with sandpaper and immersed in sodium hydroxide solution to remove the oxide layer, oil stains and rust on the surface, the hexafluorozirconic acid aqueous solution and the silane hydrolyzate are hybridized, and a film layer is formed on the steel fiber through the synergistic effect of zirconium salt and silane, thereby improving the corrosion resistance and bonding properties of the steel fiber.

[0011] Optionally, the silane is selected from one or more of aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, and aminopropyltrimethoxysilane.

[0012] By adopting the above technical solution, the above silane can increase the roughness of the steel fiber surface, so that the bonding force of the steel fiber in the cement matrix is ​​increased.

[0013] Optionally, the silane is a mixture of aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane in a volume ratio of (0.7-0.9):1.

[0014] By adopting the above technical scheme, hydroxyl groups are bonded to the surface of the steel fiber after being soaked in sodium hydroxide solution. The silane compound containing amino and mercapto groups can be further combined with the active hydroxyl groups through chemical bonds. The silane with more groups introduced is highly active, which is conducive to the bridging effect between the cement matrix and the steel fiber, making the concrete interface more compact.

[0015] Optionally, the polyvinyl formal adhesive is modified polyvinyl formal adhesive, and the modified polyvinyl formal adhesive comprises the following raw materials in parts by weight: 54-58 parts of polyvinyl formal glue; Phenol 9-11 parts.

[0016] By adopting the above technical scheme, the free formaldehyde in phenol and polyvinyl formal glue is reacted, and then reacted with polyvinyl formal, so that the adhesion and water resistance of the modified polyvinyl formal glue are improved, and at the same time the solid content is increased, so that the reinforcing and toughening effect of the polymer in the cement matrix is ​​more fully exerted.

[0017] Optionally, the steel fiber is copper-plated steel fiber with a length of 20-25 mm and a diameter of 0.15-0.25 mm.

[0018] By adopting the above technical solution, the mercapto group can further chemically bond with the copper plating, further enhancing the adhesion between silane and steel fiber, thereby improving the performance of steel fiber concrete.

[0019] Optionally, the fineness modulus of the quartz sand is 2.4-2.7 and the particle size is 2-5 mm.

[0020] Optionally, the water reducer is a polycarboxylate water reducer or a naphthalene water reducer.

[0021] In a second aspect, the present application discloses a method for preparing fiber concrete, comprising the following steps: Pour cement and fly ash into a mixer and stir for 2-3 minutes, then add crushed stone and quartz sand into the mixer and stir for 2-3 minutes; evenly mix water reducer, water, polyvinyl formal glue and defoamer to obtain a mixed solution, add the mixed solution into the mixer and stir for 3-5 minutes to obtain a mixture; Disperse the steel fiber in the mixture, continue stirring for 3-4 minutes, cast and oscillate into a mold, cure and demould to obtain fiber concrete.

[0022] By adopting the above technical scheme, fiber concrete is obtained by stirring and mixing, the preparation method is simple, and the obtained concrete has excellent flexural strength and toughness and good durability.

[0023] In a third aspect, the present application discloses a manhole cover comprising a steel reinforcement skeleton and any one of the above-mentioned fiber concretes.

[0024] By adopting the above technical solution, steel fiber concrete is filled into the steel skeleton to obtain a manhole cover with high bearing capacity and good durability.

[0025] In summary, the present application has at least one of the following beneficial effects: The concrete prepared by the present application through the combination of specific components has excellent flexural strength, corrosion resistance and durability, and the steel fiber concrete manhole cover produced has large bearing capacity and strong durability.

[0026] In fiber concrete, silane-modified steel fiber is selected. The bonding strength between steel fiber and cement matrix is ​​improved through silane modification, and the interface transition zone between steel fiber and cement matrix is ​​improved, so that the bridging and reinforcing effects of steel fiber can be more fully exerted to control the generation of cracks; at the same time, silane forms a surface coating on the surface of steel fiber, which is beneficial to the improvement of steel fiber anti-corrosion and the durability of steel fiber concrete manhole cover. The addition of fly ash can reduce the enrichment of calcium hydroxide content and increase the interface bonding force. The addition of polyvinyl alcohol formal glue can react with cement components to increase bonding force, fill the gaps in cement to enhance toughness, and improve the interface structure between steel fiber and cement matrix together with silane, so that the flexural strength and toughness of concrete are improved, and the bearing capacity and durability of concrete manhole cover are improved. DETAILED DESCRIPTION

[0027] The present application is further described in detail below.

[0028] The cement is 42.5 grade ordinary Portland cement; The quartz sand used has a fineness modulus of 2.5 and a particle size of 2-5mm; Polycarboxylate water reducer, Shandong Tianfeng Chemical Technology Co., Ltd.; Naphthalene-based water reducer, Jinan Yucai Chemical; The fly ash is Class I fly ash; Steel fiber: copper-plated steel fiber from Shandong Hongju Engineering Materials Co., Ltd., length 20-25mm, diameter 0.15-0.25mm; polyvinyl formal glue, 107 glue from Guangzhou Shuangpu Trading Co., Ltd.

[0029] Preparation Example Preparation Example 1 Preparation of silane-modified steel fibers Mix water, methanol and aminopropyltriethoxysilane in a volume ratio of 5:1:1, add acetic acid to adjust the pH to 4 to obtain a silane hydrolyzate, add a certain amount of a hexafluorozirconic acid aqueous solution with a mass fraction of 45% to the silane hydrolyzate to obtain a silane hydrolyzate with a mass fraction of hexafluorozirconic acid of 6%; The steel fibers were polished with sandpaper, soaked in sodium hydroxide solution for 30 min, taken out, washed with deionized water and ethanol, and dried naturally; The air-dried steel fiber was immersed in a silane hydrolyzate, taken out and placed in an oven at 100° C. for 20 minutes to obtain a silane-modified steel fiber.

[0030] Preparation Example 2 Preparation of silane-modified steel fibers Water, methanol and vinyltrimethoxysilane are mixed in a volume ratio of 6:1.3:1, acetic acid is added to adjust the pH to 6 to obtain a silane hydrolyzate, and a certain amount of a hexafluorozirconic acid aqueous solution with a mass fraction of 45% is added to the silane hydrolyzate to obtain a silane hydrolyzate with a mass fraction of hexafluorozirconic acid of 9%; The steel fibers were polished with sandpaper, soaked in sodium hydroxide solution for 40 min, taken out, washed with deionized water and ethanol, and dried naturally; The air-dried steel fiber was immersed in a silane hydrolyzate, taken out and placed in an oven at 110° C. for 30 minutes to obtain a silane-modified steel fiber.

[0031] Preparation Example 3 Preparation of silane-modified steel fibers Water, methanol, aminopropyltrimethoxysilane and vinyltrimethoxysilane are mixed in a volume ratio of 5.5:1.1:0.5:0.5, acetic acid is added to adjust the pH to 5 to obtain a silane hydrolyzate, and a certain amount of a hexafluorozirconic acid aqueous solution with a mass fraction of 45% is added to the silane hydrolyzate to obtain a silane hydrolyzate with a mass fraction of hexafluorozirconic acid of 8%; The steel fibers were polished with sandpaper, soaked in sodium hydroxide solution for 35 min, taken out, washed with deionized water and ethanol, and dried naturally; The air-dried steel fiber was immersed in a silane hydrolyzate, taken out and placed in an oven at 105° C. for 25 minutes to obtain a silane-modified steel fiber.

[0032] Preparation Example 4 Preparation of silane-modified steel fibers The difference between this preparation example and preparation example 1 is that the silane is a mixture of aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane in a volume ratio of 0.7:1, and the volume ratio of water, methanol, aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane is 5:1:0.41:0.59.

[0033] Preparation Example 5 Preparation of silane-modified steel fibers The difference between this preparation example and preparation example 1 is that the silane is a mixture of aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane in a volume ratio of 0.7:1, and the volume ratio of water, methanol, aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane is 5:1:0.41:0.59.

[0034] Preparation Example 6 Preparation of modified polyvinyl formal glue: 9 parts of phenol were added to 54 parts of polyvinyl formal glue with a solid content of 12%, the temperature was raised to 80°C, the reaction was kept warm for 0.5h, the temperature was lowered to 60°C, the pH was adjusted to 7 with sodium hydroxide, and the glue was cooled to room temperature to obtain modified polyvinyl formal glue.

[0035] Preparation Example 7 Preparation of modified polyvinyl formal glue: 11 parts of phenol were added to 58 parts of polyvinyl formal glue with a solid content of 10%, the temperature was raised to 85°C, the reaction was kept warm for 1 hour, the temperature was lowered to 60°C, the pH was adjusted to 7 with sodium hydroxide, and the mixture was cooled to room temperature to obtain modified polyvinyl formal glue. Example

[0036] Example 1 Preparation of fiber concrete Fiber concrete comprises the following raw materials in parts by weight: Cement 180kg, crushed stone 310kg, quartz sand 220kg, Silane-modified steel fiber 18kg: The silane-modified steel fiber prepared in Preparation Example 1 is selected. 38kg fly ash, 1kg polycarboxylate water reducer, 2.4kg polyvinyl formal glue, 42kg water, Defoaming agent 0.1kg: Use polyoxypropylene ether defoaming agent, Guangzhou Du Te Chemical Co., Ltd., model AEO-7.

[0037] A method for preparing fiber concrete comprises the following steps: Pour cement and fly ash into a mixer and mix for 2 minutes, then add crushed stone and quartz sand into the mixer and mix for 2 minutes; The water reducing agent, water, polyvinyl formal glue and defoamer are uniformly mixed to obtain a mixed solution, and the mixed solution is added into a blender and stirred for 3 minutes to obtain a mixture; Disperse the steel fiber in the mixture, continue stirring for 3 minutes, cast and oscillate into a mold, and then perform curing and demoulding to obtain fiber concrete.

[0038] Example 2 Preparation of fiber concrete Fiber concrete comprises the following raw materials in parts by weight: Cement 230kg, crushed stone 350kg, quartz sand 270kg, Silane-modified steel fiber 23kg: The silane-modified steel fiber prepared in Preparation Example 2 was selected. 43kg fly ash, 2kg polycarboxylate water reducer, 3.8kg polyvinyl formal glue, 49kg water, Defoaming agent 0.3kg: Use polyoxypropylene ether defoaming agent, Guangzhou Du Te Chemical Co., Ltd., model AEO-7.

[0039] A method for preparing fiber concrete comprises the following steps: Pour cement and fly ash into a mixer and mix for 3 minutes, then add crushed stone and quartz sand into the mixer and mix for 3 minutes; The water reducing agent, water, polyvinyl formal glue and defoamer are uniformly mixed to obtain a mixed solution, and the mixed solution is added into a mixer and stirred for 5 minutes to obtain a mixture; Disperse the steel fiber in the mixture, continue stirring for 4 minutes, cast and oscillate into a mold, and then perform curing and demoulding to obtain fiber concrete.

[0040] Example 3 Preparation of fiber concrete Fiber concrete comprises the following raw materials in parts by weight: Cement 210kg, crushed stone 320kg, quartz sand 240kg, Silane-modified steel fiber 21kg: The silane-modified steel fiber prepared in Preparation Example 3 was selected. 40kg fly ash, 1.5kg polycarboxylate water reducer, 3kg polyvinyl formal glue, 47kg water, Defoaming agent 0.2kg: Use silicone defoaming agent, Guangzhou Jincheng Chemical Co., Ltd., model PMX-200.

[0041] A method for preparing fiber concrete comprises the following steps: Pour cement and fly ash into a mixer and mix for 2 minutes, then add crushed stone and quartz sand into the mixer and mix for 3 minutes; The water reducing agent, water, polyvinyl formal glue and defoamer are uniformly mixed to obtain a mixed solution, and the mixed solution is added into a mixer and stirred for 5 minutes to obtain a mixture; Disperse the steel fiber in the mixture, continue stirring for 3 minutes, cast and oscillate into a mold, and then perform curing and demoulding to obtain fiber concrete.

[0042] Example 4 The only difference between this embodiment and embodiment 1 is that the silane-modified steel fiber is the silane-modified steel fiber prepared in preparation example 4.

[0043] Example 5 The only difference between this embodiment and embodiment 1 is that the silane-modified steel fiber is the silane-modified steel fiber prepared in preparation example 5.

[0044] Example 6 The only difference between this embodiment and embodiment 1 is that the polyvinyl formal adhesive is the modified polyvinyl formal adhesive prepared in preparation example 6.

[0045] Example 7 The only difference between this embodiment and embodiment 1 is that the polyvinyl formal adhesive is the modified polyvinyl formal adhesive prepared in preparation example 7.

[0046] Example 8 The only difference between this embodiment and embodiment 1 is that the silane-modified steel fiber is the silane-modified steel fiber prepared in preparation example 5, and the polyvinyl formal adhesive is the modified polyvinyl formal adhesive prepared in preparation example 6.

[0047] Example 9 The only difference between this embodiment and embodiment 1 is that the silane-modified steel fiber is the silane-modified steel fiber prepared in preparation example 4, and the polyvinyl formal adhesive is the modified polyvinyl formal adhesive prepared in preparation example 7.

[0048] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, steel fibers of equal mass are selected to replace the silane-modified steel fibers.

[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, no polyvinyl formal glue and defoaming agent are added to the raw materials of the fiber concrete.

[0050] Performance Testing The concrete prepared in the embodiment and the comparative example was cast into a standard test piece with a side length of 100 mm*100 mm*100 mm, and wet-cured for 20 days and dry-cured for 8 days. The relevant performance data after curing for 28 days was measured.

[0051] 1. Compressive strength: Test according to Chapter 5 Compressive strength test of GB / T 50081-2002 Standard for Test Methods of Mechanical Properties of Ordinary Concrete, and record the compressive strength (MPa).

[0052] 2. Flexural strength: Test according to Chapter 10 Flexural strength test of GB / T 50081-2002 Test methods for mechanical properties of ordinary concrete, and record the flexural strength (MPa).

[0053] 3. Sulfate corrosion resistance test: Determine according to the sulfate corrosion resistance test method in GB / T 50082-2009 Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete, and record the corrosion resistance grade KS.

[0054] Table 1 Sample Compressive strength / MPa Flexural strength / MPa Corrosion resistance grade KS Example 1 82.6 19.9 KS150 Example 2 81.2 21.5 KS150 Example 3 84.7 22.8 KS150 Example 4 93.7 29.6 KS150 Example 5 91.4 29.1 KS150 Example 6 86.3 23.9 KS150 Example 7 87.0 24.3 KS150 Example 8 99.6 33.2 KS150 and above Example 9 100.2 33.5 KS150 and above Comparative Example 1 59.2 7.6 KS60 Comparative Example 2 65.8 13.4 KS90 Data analysis According to the data in Table 1, the fiber concrete of the present application is prepared by compounding silane-modified steel fiber and polyvinyl formal adhesive, and by matching specific components, the compressive strength of the fiber concrete is greater than 80MPa, reaching the C80 standard, and the flexural strength is improved. The steel fiber is modified by silane, and the interface structure is improved by polyvinyl formal adhesive, so that the toughness and corrosion resistance of the concrete are improved.

[0055] By comparing Examples 4-5 with Examples 1-3, it is shown that there are differences in the modification effects of different silanes on steel fibers. When a mixture of aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane is used, the overall performance of the concrete is better. It is speculated that this may be because silane introduces amino and mercapto groups, which are more active, so that the cross-linking and bridging effect of silane on steel fibers and cement matrix is ​​stronger; mercaptosilane and steel fibers form a Cu-S chemical bond with higher chemical bonding force, and there is a chemical bond force between the amino group and the active hydroxyl group of the cement matrix, which makes the concrete interface firm, and the compressive strength, flexural strength and crack resistance are improved.

[0056] By comparing Examples 6-7 with Example 1, it is shown that the performance of concrete is improved after the polyvinyl alcohol formal glue is modified. This may be because the addition of phenol reacts with free formaldehyde and then reacts with polyvinyl alcohol formal for a secondary reaction, the solid content of 107 glue is increased, and the bonding strength is improved, which is more conducive to the reaction between polyvinyl alcohol formal glue and cement components and the strengthening and toughening effect on cement, so that the performance of concrete is improved.

[0057] Comparison of Comparative Examples 1-2 with Example 1 shows that silane was not used to modify the steel fiber in Comparative Example 1, and polyvinyl formal was not used in Comparative Example 2, and the performance of the concrete decreased. This may be because the addition of steel fiber reinforces the concrete, but the bonding strength between the steel fiber and the cement matrix decreases, resulting in the inability to fully exert the role of the steel fiber, which illustrates the synergistic effect of silane and polyvinyl formal.

[0058] Application Examples Application Example 1 A manhole cover includes a steel frame and fiber concrete, wherein the fiber concrete is the fiber concrete prepared in Example 1. The method for preparing the manhole cover includes the following steps: A mold for a manhole cover is made, and a steel skeleton is placed in the mold. A concrete filling part is formed by multiple steel bars. The prepared concrete is placed in the concrete filling part, steam-cured to the demoulding strength, and demoulding is performed to obtain a concrete manhole cover.

[0059] The manhole cover also includes a steel hoop. A prism-shaped steel hoop made of steel plate is arranged around the concrete manhole cover. The taper is 1:10. Steel bar hoops; the edging steel hoops are treated with rust prevention before leaving the factory.

[0060] Application Example 2-9 and Comparative Application Example 1-2 The difference between Application Examples 2-9 and Comparative Application Examples 1-2 and Application Example 1 is that: the fiber concrete used is different.

[0061] Application Examples 2-9 and Comparative Application Examples 1-2 use the fiber concrete prepared in Examples 2-9 and Comparative Examples 1-2, respectively.

[0062] Performance test of manhole cover: Bearing capacity of manhole cover: According to the method of GB / T 26537-2011 "Steel Fiber Concrete Inspection Manhole Cover", the crack load and failure load of the manhole cover are measured respectively and recorded in Table 2.

[0063] Table 2 Sample Crack load / kN Destruction load / kN Application Example 1 138.8 285.5 Application Example 2 137.7 283.7 Application Example 3 141.6 289.1 Application Example 4 147.5 308.6 Application Example 5 148.1 314.8 Application Example 6 153.8 327.5 Application Example 7 153.2 326.2 Application Example 8 177.9 351.3 Application Example 9 178.3 353.4 Comparative application example 1 126.5 254.5 Comparative Application Example 2 129.4 268.7 Data analysis According to the data in Table 2, the concrete manhole cover prepared in this application has a high bearing capacity, which meets the standard requirements of crack load ≥ 125kN and failure load ≥ 250kN. After the steel fiber is modified by silane, silane forms a protective film layer on the surface of the steel fiber, which improves the corrosion resistance of the steel fiber, thereby improving the durability of the concrete manhole cover.

[0064] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fiber concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 180-230 parts of cement; 310-350 parts of crushed stone; Quartz sand 220-270 parts; 18-23 parts of silane modified steel fiber; 38-43 parts of fly ash; 1-2 parts of water reducing agent; 2.4-3.8 parts of polyvinyl formal glue; 42-49 parts of water; Defoaming agent 0.1-0.3 parts.

2. A fiber concrete according to claim 1, characterized in that: The silane-modified steel fiber is prepared by the following steps: Mix water, methanol and silane in a volume ratio of (5-6):(1-1.3):1, add acetic acid to adjust the pH to 4-6 to obtain a silane hydrolyzate, add an aqueous solution of hexafluorozirconic acid to the silane hydrolyzate to obtain a silane hydrolyzate having a mass fraction of hexafluorozirconic acid of 6%-9%; The steel fiber was polished with sandpaper, soaked in sodium hydroxide solution for 30-40 min, taken out, washed with deionized water and ethanol, and dried naturally; The air-dried steel fiber is immersed in a silane hydrolyzate, taken out and placed in an oven at 100-110° C. for drying to obtain a silane-modified steel fiber.

3. The fiber concrete according to claim 1, characterized in that: The silane is selected from one or more of aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane and aminopropyltrimethoxysilane.

4. A fiber concrete according to claim 3, characterized in that: The silane is a mixture of aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane in a volume ratio of (0.7-0.9):

1.

5. The fiber concrete according to claim 1, characterized in that: The polyvinyl formal adhesive is modified polyvinyl formal adhesive, and the modified polyvinyl formal adhesive comprises the following raw materials in parts by weight: 54-58 parts of polyvinyl formal glue; Phenol 9-11 parts.

6. The fiber concrete according to claim 2, characterized in that: The steel fiber is copper-plated steel fiber with a length of 20-25 mm and a diameter of 0.15-0.25 mm.

7. The fiber concrete according to claim 1, characterized in that: The fineness modulus of the quartz sand is 2.4-2.7, and the particle size is 2-5 mm.

8. The fiber concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent or a naphthalene water reducing agent.

9. The method for preparing fiber concrete according to any one of claims 1 to 8, characterized in that: The steps include: Pour cement and fly ash into the mixer and mix for 2-3 minutes, then add crushed stone and quartz sand into the mixer and mix for 2-3 minutes; The water reducing agent, water, polyvinyl formal glue and defoamer are uniformly mixed to obtain a mixed solution, and the mixed solution is added into a mixer and stirred for 3-5 minutes to obtain a mixture; Disperse the steel fiber in the mixture, continue stirring for 3-4 minutes, cast and oscillate into a mold, cure and demould to obtain fiber concrete.

10. A manhole cover, characterized in that: It comprises a steel skeleton and a fiber concrete as described in any one of claims 1-8.